Severe Acute Respiratory Syndrome Coronavirus 2 Infection among Returnees to Japan from Wuhan, China, 2020 - Arima, Yuzo; Kutsuna, Satoshi; Shimada, Tomoe; Suzuki, Motoi; Suzuki, Tadaki; Kobayashi, Yusuke; Tsuchihashi, Yuuki; Nakamura, Haruna; Matsumoto, Kaoru; Takeda, Asuka; Kadokura, Keisuke; Sato, Tetsuro; et al. (Emerging infectious diseases, 2020)
In early 2020, Japan repatriated 566 nationals from China. Universal laboratory testing and 14-day monitoring of returnees detected 12 cases of severe acute respiratory syndrome coronavirus 2 infection; initial screening results were negative for 5. Common outcomes were remaining asymptomatic (n = 4) and pneumonia (n = 6). Overall, screening performed poorly.